Decolorization of textile indigo dye by ligninolytic fungi - Balan, DSL; Monteiro, RTR (Elsevier B.V., 2001)
The indigo dye is extensively used by textile industries and is considered a recalcitrant substance, which causes environmental concern. Chemical products used on textile processing, which affect the environment through effluents, can be voluminous, colored and varied. Vat textile dyes, like indigo, are often used and dye mainly cellulosic fibers of cotton. Decolorization of this dye in liquid medium was tested with ligninolytic basidiomycete fungi from Brazil. Decolorization started in a few hours and after 4 days the removal of dye by Phellinus gilvus culture was in 100%, by Pleurotus sajor-caju 94%, by Pycnoporus sanguineus 91% and by Phanerochaete chrysosporium 75%. No color decrease was observed in a sterile control. Thin layer chromatography of fungi culture extracts revealed only one unknown metabolite of Rf = 0.60, as a result of dye degradation. (C) 2001 Published by Elsevier B.V. B.V.
Keywords: ligninolytic fungi; indigo; textile industries; decolorization